Examination of factor structure of the inventory of complicated grief (ICG) in a sample of bereaved military family members with persistent and elevated grief. Issue 3 (30th June 2017) - Fisher, Joscelyn E.; Mauro, Christine; Cozza, Stephen J.; Wall, Melanie; Simon, Naomi M.; Ortiz, Claudio D.; Harrington‐LaMorie, Jill; Wang, Yuanjia; Fullerton, Carol S.; Ursano, Robert J.; Katherine Shear, M.
Abstract: Knowledge about the effect of a US service member's death on surviving family members is limited. In order to identify their grief‐related health care needs, a first step is to identify the characteristics of persistent and elevated grief in a military family sample. The present study identified military family members ( n = 232) bereaved more than six months who endorsed an elevated level of grief. A confirmatory factor analysis and test of measurement invariance of factor structure were used to compare the factor structure of their Inventory of Complicated Grief (ICG) responses to that of a bereaved non‐military‐related clinical research sample with similar grief levels. Results confirmed an equivalent five‐factor structure of the ICG in both the military family sample and the clinical research sample. The similarity in factor structure was present despite differences in demographic characteristics and bereavement experiences between samples. Thus, the ICG reliably measures persistent and elevated grief in military family samples and provides grief symptom profiles that facilitates better understanding of their grief‐related needs.